STIGMA TOWARDS PEOPLE LIVING WITH HIV/AIDS AMONG COUNSELING OFFICERS IN SOUTH SULAWESI, INDONESIA - Abd Risal; Andi Masyitha Irwan; Elly Lilianty Sjattar (Belitung Nursing Journal, 2018)
Background: Human Immunodeficiency Virus (HIV) / Acquired Immunodeficiency Syndrome (AIDS) has become a global problem nowadays. To reduce its spread, Voluntary Counseling and Testing (VCT) and Provider-Initiated Testing and Counseling (PITC) have been provided. However, these interventions remain ineffective to discover new cases, as the stigma among health officers may exist. Objective: To compare the stigma towards people living with HIV/AIDS between VCT and PITC officers. Methods: This was a descriptive comparative study conducted in Makassar City, Parepare City and Sidenreng Rappang Regency, South Sulawesi Province, Indonesia. There were 139 samples were selected using a convenience sampling technique, which consisted of 66 VCT counseling officers and 73 PITC officers. The questionnaire from Health Policy Project in Thailand was used to measure the HIV/AIDS related-stigma. Data were analyzed using descriptive statistics and Mann Whitney test. Results: Findings showed that there was a statistically significant difference in stigma between the group of VCT and PITC on people living with HIV/AIDS (PLWHA), which the mean of stigma in the PITC group (73.07) was higher than the mean value in the VCT group (66.61). Conclusion: There was a significant difference in stigma between VCT and PITC officers towards PLWHA. It is suggested that PITC curriculum should be evaluated, and supervision and monitoring in both VCT and PITC groups should be implemented regularly to reduce the stigma towards PLWHA.